Crossed [compact disc, unabridged] - Condie, Allyson Braithwaite (Condie, Allyson Braithwaite. Matched trilogy, 2011)
Seventeen-year-old Cassia sacrifices everything and heads to the Outer Provinces in search of Ky, where she is confronted with shocking revelations about Society and the promise of rebellion.